2005
DOI: 10.1590/s1806-37132005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo fenotípico e genotípico da resistência aos macrolídeos de "Streptococcus pneumoniae" isolados em hospitais de Porto Alegre - RS

Abstract: OBJETIVO: O objetivo deste estudo foi determinar a prevalência do S. pneumoniae resistente aos macrolídeos e identificar suas características fenotípicas e genotípicas. MÉTODOS: Amostras de S. pneumoniae isoladas entre maio de 2002 e agosto de 2004, em Porto Alegre (RS), a partir de materiais clínicos coletados de diferentes sítios anatômicos foram analisadas. Para o teste de difusão em ágar foram utilizados discos de eritromicina, claritromicina, azitromicina e clindamicina. As concentrações inibitórias mínim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…(2) A study carried out by Zettler et al in five hospitals in the city of Porto Alegre and published in this issue of the Brazilian Journal of Pulmonology (3) revealed that 5.2% of the pneumococcal strains isolated were resistant to erythromycin, a value similar to the 4.3% found among samples isolated in three Brazilian states from 1990 to 1999. (4) The two mechanisms of resistance found were alteration in the bacterial ribosome, with a decrease in the affinity for antimicrobials (MSLB phenotype), and alteration in the active efflux, in order to remove drugs from the cytoplasm of the microorganism (M phenotype).…”
mentioning
confidence: 81%
“…(2) A study carried out by Zettler et al in five hospitals in the city of Porto Alegre and published in this issue of the Brazilian Journal of Pulmonology (3) revealed that 5.2% of the pneumococcal strains isolated were resistant to erythromycin, a value similar to the 4.3% found among samples isolated in three Brazilian states from 1990 to 1999. (4) The two mechanisms of resistance found were alteration in the bacterial ribosome, with a decrease in the affinity for antimicrobials (MSLB phenotype), and alteration in the active efflux, in order to remove drugs from the cytoplasm of the microorganism (M phenotype).…”
mentioning
confidence: 81%